The God father 1 - Coppola, Francis Ford (Los Angeles, CA Paramount Pictures Corporation, 1972)
In late August 1945[5], as the movie opens, Don Vito Corleone (Marlon Brando) and consigliere Tom Hagen (Robert Duvall) hear requests for favors during the Don's daughter Connie's wedding reception. Singer Johnny Fontane (Al Martino), Corleone's godson, asks for help in landing a movie role that will revitalize his flagging career. Hagen is dispatched to California to meet with studio head Jack Woltz (John Marley). After initially refusing to cast Fontane, Woltz caves in when he finds the severed head of his prized racehorse "Khartoum" in his bed the next morning. Upon Hagen's return, the family leadership meets with Virgil "The Turk" Sollozzo (Al Lettieri), who asks Don Corleone to protect the rival Tattaglia family's planned heroin business. Don Vito disapproves of drug trafficking and feels his political influence could be jeopardized and he rejects the potentially lucrative proposal. He then sends his primary enforcer, Luca Brasi (Lenny Montana), to infiltrate Sollozzo's organization, but Brasi is stabbed in the hand by Sollozzo and garroted to death by Bruno Tattaglia. Don Corleone is shot five times in the back at a fruit stand in an assassination attempt. Sollozzo abducts Hagen and persuades him to offer Corleone's eldest son, Sonny (James Caan), the deal previously offered to the Don. The youngest son, Michael (Al Pacino), whom the other Mafia families consider a "civilian" uninvolved in mob business, averts a second murder attempt at the hospital where his father is being treated, but his jaw is broken by corrupt Irish American police Captain McCluskey (Sterling Hayden). Sonny retaliates by having Don Philip Tattaglia's son, Bruno, killed. Sollozzo and McCluskey meet with Michael at a local Italian restaurant in an attempt to settle the dispute. Michael pretends he needs to use the bathroom, and following a plan he initiated, retrieves a gun hidden there. Michael returns to the table and kills both Sollozzo and McCluskey. He leaves the country and takes refuge in Sicily, where he soon marries a young local woman named Apollonia Vitelli (Simonetta Stefanelli). The third Corleone brother, Fredo (John Cazale), is sent to Las Vegas where he is sheltered by casino operators the Corleones financially back. Open warfare soon erupts between the Corleones and the other members of the Five Families, while the police and other authorities begin to clamp down on Mafia activity. Don Vito is particularly distressed when he learns of Michael's involvement, since he had planned for Michael to remain uninvolved in the "family business." Sonny impulsively leaves the guarded family compound to confront Carlo (Gianni Russo) who has been abusing Connie (Talia Shire). Sonny beats Carlo on the street and threatens to kill him if he ever touches Connie again. A few days later Carlo beats Connie again, and upon getting her phone call, Sonny leaves the compound again. En route, he is ambushed and killed at a toll booth. Meanwhile, Michael narrowly escapes death in Sicily when his wife is killed by a car bomb. Don Vito meets with the other Five Family dons and settles their dispute, withdrawing his opposition to the Tattaglia's heroin business. He deduces from the negotiations that the Tattaglias were acting on behalf of the more powerful Don Barzini (Richard Conte). With his safety now guaranteed, Michael returns home. More than a year later, he marries his long time American girlfriend, Kay Adams (Diane Keaton). As his father withdraws from active control of the Corleone family, and as middle brother Fredo is seen as incapable of shouldering the Don's responsibilities, Michael takes control of the family and its business. He promises Kay he will legitimize its businesses within five years. Biding his time, Michael allows rival families to pressure Corleone enterprises and eat away at their revenues, disturbing several of his caporegimes. He directs them not to retaliate, disclosing plans to move family operations to Nevada while spinning off New York operations to family members who stay behind. Michael chooses Carlo to go to Vegas and replaces Hagen with a new consigliere; Vito explains to the upset Hagen that he and Michael have longer-range plans for him and for the family. Michael travels to Las Vegas, intending to buy out their casino partner, Moe Greene (Alex Rocco). Greene angrily rejects the proposal, deriding the Corleones as a failing organization. Michael is particularly angered when Fredo, under the sway of Greene and his associates, warns his brother that Greene is too important to be treated in that fashion. Vito Corleone collapses and dies while playing with his young grandson Anthony in his tomato garden. At the burial, caporegime Tessio (Abe Vigoda) arranges a meeting between Michael and Don Barzini, now seen as the dominant figure in the New York families. As Vito had warned Michael, Tessio's involvement signals his shift of allegiance to the Barzini family; the planned meeting is intended to result in Mic
color 2:48 Min